Plan de cuidado de enfermería en paciente con insuficiencia renal crónica - Aviles Mora, Esthela Solandy (2018)
The present case study is based on making known the most relevant parts of the risk of manifesting chronic renal failure and on what measures to take by the nursing staff to avoid harmful effects that compromise the patient's health. Chronic renal failure is defined as the presence of persistent renal damage for at least 3 months, secondary to the slow, progressive and irreversible reduction of the number of nephrons with the consequent clinical syndrome derived from the renal inability to carry out depurative, excretory functions, regulatory and endocrine metabolic. OBJECTIVE: To apply the nursing procedures in patients with chronic renal failure to improve the quality of life. CONCLUSIONS: In this way it was possible to identify the risk factors that predisposed the patient's state of health, in which all the knowledge acquired in the years of study was put into practice. By applying the nursing care process, interventions were made according to the needs evidenced in the death of the patterns required by the patient and to achieve their improvement. By which the improvement of the patient was obtained, predominating with its successful treatment